Guidelines for visualization and analysis of DC in tissues using multiparameter fluorescence microscopy imaging methods - Bayerl, Felix; Bejarano, David A.; Bertacchi, Giulia; Doffin, Anne Claire; Gobbini, Elisa; Hubert, Margaux; Li, Lijian; Meiser, Philippa; Pedde, Anna Marie; Posch, Wilfried; Rupp, Luise; Schlitzer, Andreas; et al. (European Journal of Immunology, 2023)
This article is part of the Dendritic Cell Guidelines article series, which provides a collection of state-of-the-art protocols for the preparation, phenotype analysis by flow cytometry, generation, fluorescence microscopy, and functional characterization of mouse and human dendritic cells (DC) from lymphoid organs and various non-lymphoid tissues. Here, we provide detailed procedures for a variety of multiparameter fluorescence microscopy imaging methods to explore the spatial organization of DC in tissues and to dissect how DC migrate, communicate, and mediate their multiple functional roles in immunity in a variety of tissue settings. The protocols presented here entail approaches to study DC dynamics and T cell cross-talk by intravital microscopy, large-scale visualization, identification, and quantitative analysis of DC subsets and their functions by multiparameter fluorescence microscopy of fixed tissue sections, and an approach to study DC interactions with tissue cells in a 3D cell culture model. While all protocols were written by experienced scientists who routinely use them in their work, this article was also peer-reviewed by leading experts and approved by all co-authors, making it an essential resource for basic and clinical DC immunologists.
CRIS-Team Scopus Importer:2023-01-20